2015
DOI: 10.1615/jlongtermeffmedimplants.2014010812
|View full text |Cite
|
Sign up to set email alerts
|

Implant Fracture after Long-Stemmed Cemented Hemiarthroplasty for Oncologic Indications

Abstract: Although a long-stemmed cemented hemiarthroplasty is frequently recommended for oncologic lesions of proximal femur, we have observed an alarming number of spontaneous stem fractures. The purpose of this retrospective study was to identify the associated risk factors for stem fractures in a study cohort of 60 (61 prostheses) during 1983-2007. At a mean follow-up of 41 months, 4/61 (6.6%) stems had fractured after a mean of 36 (12-92) months after surgery. All failed implants were Osteonics Omnifit (4/27; 14.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Peterson et al reported fair levels of function among 21 patients treated with long stem cemented hemiarthroplasty in 22 limbs for metastases 11 . However, Maheshwari et al reported 6.6% stem fracture rate among 61 long stem cemented hemiarthroplasty performed for oncologic indications 12 . The cost of long stem bipolar hemiarthroplasty in our setting is around USD 1,700.…”
Section: Discussionmentioning
confidence: 99%
“…Peterson et al reported fair levels of function among 21 patients treated with long stem cemented hemiarthroplasty in 22 limbs for metastases 11 . However, Maheshwari et al reported 6.6% stem fracture rate among 61 long stem cemented hemiarthroplasty performed for oncologic indications 12 . The cost of long stem bipolar hemiarthroplasty in our setting is around USD 1,700.…”
Section: Discussionmentioning
confidence: 99%